Vertebral Artery Arising From the Aortic Arch - A Study of Its Incidence - D. K., Dr. Shylaja; N, Dr. Balachandra; Ramesh, Dr. B. R. (International Journal of Innovative Research in Medical Science, 2016)
The vertebral artery (VA) is clinically described as the first branch of the ipsilateral subclavian artery. However, multiple variations in the origin of that vessel have been reported in the literature. This variation in the origin of VA is asymptomatic. Although anomalous origins of the aortic arch branches are merely anatomic variants, knowledge of variations in the branching pattern of the aortic arch is of great importance. In patients who have to undergo four-vessel angiography, aortic instrumentation, or supra-aortic thoracic, head and neck surgery. It has been reported that anomalies of the aortic arch branching pattern could lead to cerebral abnormalities by altering the pattern of flow in cerebral vessels. In addition, knowledge of abnormal branches originating from the aortic arch is also important in the diagnosis of intracranial aneurysms following subarachnoid hemorrhage. Methodology: Formalin fixed cadavers given to I MBBS students of DR B R Ambedkar Medical College, for dissection of Head & Neck, by dissection method. Results: 2 cadavers had vertebral artery arising from the arch of aorta.